Narrative of Chinese and Western Popular Fiction Comparison and Interpretation - Huang, Yonglin (Springer Berlin Heidelberg, 2018)
This book presents a comprehensive and systematic study of the narrative history and narrative methods of Chinese and Western popular fiction from the perspectives of narratology, comparative literature, and art and literature studies by adopting the methodology of parallel comparison. The book is a pioneering work that systematically investigates the similarities and differences between Chinese and Western popular fiction, and traces the root causes leading to the differences. By means of narrative comparison, it explores the conceptual and spiritual correlations and differences between Chinese and Western popular fiction and, by relating them to the root causes of cultural spirit, allows us to gain an insight into the cultural heritage of different nations. The book is structured in line with a cause-and-effect logical sequence and moves from the macroscopic to the microscopic, from history to reality, and from theory to practice. The integration of macro-level theoretical studies and micro-level case studies is both novel and effective. This book was awarded Second Prize at the Sixth Outstanding Achievement Awards in Scientific Research for Chinese Institutions of Higher Learning (Humanities & Social Sciences, 2013).